The effect of the 2013 tobacco tax increase on the expenditure patterns of Filipino smokers - Mendoza, Mauie C.; Milag, Franchelle Anne T.; Gonzales, Margarita D. (Quezon City School of Economics, University of the Philippines Diliman, 2018)
The primary goals of the recent tobacco tax changes in the Philippines are to decrease tobacco consumption and increase government revenues. Last 2013, Republic Act 10351 (RA 10351) or the "Sin Tax Law" was implemented to increase tobacco taxes which automatically increases the product's price. This paper intends to investigate if the main goals of the tax reform were attained by examining its impacts on the behavior of low and high-income families in the Philippines. Comparing 2012 and 2015 data from the Family Income and Expenditure Survey (FIES), we analyzed the changes in shares of tobacco expenditures in the country with respect to total expenditure per income decile. To further recognize the effects, we considered inequality as a factor in deciding whether the tobacco tax increase was regressive or progressive. Our results show that relative to average total expenditure, lower-income deciles have higher average shares of tobacco expenditures compared to upper-income deciles, so they therefore become the greater bearer of the tobacco tax which makes the tax regressive. However, its impact was apparently minimal, as the Gini coefficient displayed a decrease from 2012 to 2015.
Thesis (B.S. Business Economics) -- University of the Philippines Diliman
Keywords: Philippines; Tobacco products -- Taxation -- Philippines; Smoking -- Economic aspects -- Philippines